Kinematics of the orbital movement of a digital X-ray scanner of annular pipe seams; MATEC Web of Conferences; Vol. 158 : Space Engineering - Vasilchenko R. Rostislav; Simankin F. A. Fedor Arkadievich; Ziyakaev G. R. Gregory Rakitovich; Simankin A. Arkadiy (2018, 2018)
Title screen